2009
DOI: 10.1007/s10654-009-9388-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of DNA yield and purity collected with buccal cell samples

Abstract: Buccal cells are an important source of DNA in epidemiological studies, but little is known about factors that influence amount and purity of DNA. We assessed these factors in a self-administered buccal cell collection procedure, obtained with three cotton swabs. In 2,451 patients DNA yield and in 1,033 patients DNA purity was assessed. Total DNA yield ranged from 0.08 to 1078.0 lg (median 54.3 lg; mean 82.2 lg ± SD 92.6). The median UV 260:280 ratio, was 1.95. Samples from men yielded significantly more DNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…Most GWAS analyses are strongly embedded in the recently started Early Growth Genetics (EGG) Consortium and Early Genetics and Longitudinal Epidemiology (EAGLE) Consortium, in which several birth cohort studies combine their GWAS efforts focused on multiple outcomes in fetal life, childhood and adolescence [160,161]. The power of large scale consortia has been shown previously [162][163][164][165][166][167][168][169][170]. Also, strategies for genetic scoring analyses are being developed to estimate predictive values of identified genetic variants [171,172].…”
Section: Biological Samplesmentioning
confidence: 99%
“…Most GWAS analyses are strongly embedded in the recently started Early Growth Genetics (EGG) Consortium and Early Genetics and Longitudinal Epidemiology (EAGLE) Consortium, in which several birth cohort studies combine their GWAS efforts focused on multiple outcomes in fetal life, childhood and adolescence [160,161]. The power of large scale consortia has been shown previously [162][163][164][165][166][167][168][169][170]. Also, strategies for genetic scoring analyses are being developed to estimate predictive values of identified genetic variants [171,172].…”
Section: Biological Samplesmentioning
confidence: 99%
“…By then, it can also serve as a GWAs dataset for both SNP frequencies and copy number variations (CNVs) in Chinese Han population. Additional publications about genetic and biomarker studies and loco-motor diseases in EJE can be found in [111][112][113][114][115][116][117][118][119][120][121]. …”
Section: Genome Wide Association Studiesmentioning
confidence: 99%
“…2 Buccal cell collection can be performed easily by a buccal swab with a cotton swab or using a mouth-wash procedure. 3 DNA isolation using buccal swabs provides many advantages, such as cost-effective processing, lower sample volume requirement, long-term archiving, and suitability of self-collection. It is more comfortable for the patient, and the buccal swabs provide sufficient DNA for the PCRs, as they demands only a few nanograms of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…It is more comfortable for the patient, and the buccal swabs provide sufficient DNA for the PCRs, as they demands only a few nanograms of DNA. 3 Human hair is one of the most common biological materials associated with legal investigations and has been used for the statistics-based population work and DNAbased analysis in criminology. 4 The most valuable method of DNA testing is short tandem repeat analysis of nuclear DNA.…”
Section: Introductionmentioning
confidence: 99%